The effect of using selected plant materials in the NPK content of trichoderma-composted corn stalk (Zea mays). - Tugbang, Donaldo Nicanor Lala (1995.)
Two types of plant substrate were composted with the aid of Trichoderma, a compost fungus activator which shortens the decomposition process of farm and agricultural wastes. Set-up A was made up only of corn stalks (Zea mays). Set-up B was composed of corn stalks (Zea mays) plus ipil-ipil (Leucaena leucocephala), kangkong and stems (Ipomoea aquatica) and banana peels (Musa paradisiaca). Analysisof the chemical decomposition of set-up A showed to 0.28 N, 0.31 P, in the form of P2O5 and 0.28 K, in the form of K2O as compared to set-up B which was 1.85 N, 2.82 P and 1.89 K. Set-up B showed significantly high levels of nitrogen, phosphorus and potassium content at 0.01 level. Hence, the compost of Set-up B proved to be a better nutritive supplement for the soil as compared to Set-up A and would therefore mean a better medium for plant growth. (NOTE: P2O5 & K2O)
Thesis (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines in the Visayas, Iloilo City.
Keywords: Corn Stalk